Utilization of Green Supply Chain Techniques in the Hungarian Automotive Industry - Gábriel, Mónika; Szegedi, Zoltán; Nick, Gábor; Pongrácz, Ferenc (Tér - Gazdaság - Ember/Journal of Region, Economy and Society, 2017)
Automotive industry is a dominant sector of the Hungarian economy in terms of export, contribution to GDP and employment. The industry is going through radical changes, and environmental issues are getting increasingly important. This study aims to present the green supply chain management practice of the Hungarian automotive sector. In our empirical research, automotive manufacturer and supplier companies were questioned about their green supply chain management activities. The results show the popularity of the different green techniques in the fields of product design, purchasing, manufacturing and logistics along the external supply chain. Green design is the less often applied field, since its techniques require large investments and the return is slow compared to the other green activities. The area of green purchasing has a large toolkit, and we’ve found big differences in the application rate of the individual techniques. The most popular green purchasing techniques are administrative ones, i.e. requiring certain documents from the supplier. Green manufacturing has a high average popularity, since it provides quick and tangible rewards to the company. The most popular techniques in green logistics aim the reduction of the environmental impact of packaging and the increasing efficiency of transportation. We have also found that investment recovery that aims to the increased efficiency of operations by using less input to the same output is quite popular, with a remarkable progress potential.